Pemanfaatan Kearifan Lokal Sasak Sebagai Bagian Pendidikan Karakter pada Siswa SD Negeri 1 Sedau - Rismawati, Lia; Sanudin (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2024)
The aim of this study is to examine the integration of religious values within Sasak traditions as a form of ethnopedagogical education in the Lombok community. Using a qualitative approach, this research analyzes how Islamic values are combined with local traditions in the daily life of the Sasak people. The study finds that religious and cultural leaders play a central role in conveying religious values through cultural ceremonies, sermons, and informal learning related to Sasak culture. Furthermore, this tradition-based education proves effective in shaping the religious and social character of the younger generation, by connecting religious teachings with relevant cultural practices. The findings of this study are expected to provide new insights into the importance of utilizing local traditions in religious and character education in multicultural societies.